The effects of a universal child benefit - Libertad Gonzalez (Institute for the Study of Labor (IZA), 2011)
I study the impact of a universal child benefit on fertility and family well-being. I exploit the unanticipated introduction of a new, sizeable, unconditional child benefit in Spain in 2007, granted to all mothers giving birth on or after July 1, 2007. The regression discontinuity-type design allows for a credible identification of the causal effects. I find that the benefit did lead to a significant increase in fertility, as intended, part of it coming from an immediate reduction in abortions. On the unintended side, I find that families who received the benefit did not increase their overall expenditure or their consumption of directly child-related goods and services. Instead, eligible mothers stayed out of the labor force significantly longer after giving birth, which in turn led to their children spending less time in formal child care and more time with their mother during their first year of life. I also find that couples who received the benefit were less likely to break up the year after having the child, although this effect was only short-term. Taken together, the results suggest that child benefits of this kind may successfully increase fertility, as well as affecting family well-being through their impact on maternal time at home and family stability.
urn:nbn:de:101:1-201110263320
Keywords: D1; H5; J1; J2; 330; child benefit; policy evaluation; fertility; regression discontinuity; labor supply; consumption; Familienleistungsausgleich; Wirkungsanalyse; Fruchtbarkeit; Mütter; Kinderbetreuung; Familiensoziologie; Konsumentenverhalten; Arbeitsangebot; Schätzung; Spanien